Synthesis and characterization of isosorbide based polycarbonates - Yum, Sugil; Kim, Hoyeon; Seo, Yongsok (Polymer (Guilford), 2019)
Despite of its non-toxicity and eco-friendliness, isosorbide (ISB) polycarbonate is difficult to use solely due to its excessive brittleness. To overcome this drawback, it is necessary to prepare high-molecular-weight ISB-based copolycarbonates with flexible diol monomers. In this research, a series of copolycarbonates of ISB, hydrogenated bisphenol A (HBPA), and diphenyl carbonate (DPC) were synthesized by melt polycondensation process using sodium methoxide (NaOMe) as a catalyst. Using NaOMe catalyst, high molecular weight ISB/HBPA copolycarbonates (Mw = 73,000–103,000 g/mol) were obtained. The incorporation of thermally stable and flexible HBPA improved the thermal stability of the copolycarbonates and the flexibility of the polymer chains to demonstrate the possibility of producing soft polycarbonates which are more environmentally friendly and can overcome the brittleness of the ISB polycarbonates. [Display omitted] •A series of copolycarbonates of ISB, hydrogenated bisphenol A (HBPA), and diphenyl carbonate (DPC) were synthesized by melt polycondensation.•High molar mass (Mw = 73000–103000 g/mol) ISB/HBPA copolycarbonates were obtained with NaOMe catalyst.•The inclusion of flexible and environmentally friendly HBPA resulted in a reduction in Young's modulus, thus, a more softer polycarbonate but an increase in elongation at break as HBPA content increased.•For the ISB/HBPA 95:5 sample demonstrates the possibility of a softer but mechanically comparable polycarbonate production.